Respostas

2014-03-26T15:42:54-03:00
F(x)= 12x-5
a) f(-2)
f(-2)= 12. (-2)-5
f(-2)= -24-5
f(-2)= -29
 
b) f(2)=12.2-5
f(2)= 24-5
f(2)=19

c)f(0)= 12.0-5
f(0)=-5

d)f(-1)= 12.(-1)-5
f(-1)=-12-5
f(-1)= -17
2014-03-26T17:07:18-03:00
F(x) = 12x - 5
f(-2) = 12.(-2) - 5 
f(-2) = -24 - 5
f(-2) = - 29
-----------------------
f(x) = 12x - 5
f(2) = 12.2 - 5
f(2) = 24 - 5 
f(2) = 19
------------------------
f(x) = 12x - 5
f(0) = 12.0 - 5
f(0) = 0 - 5
f(0) = -5
--------------------
f(x) = 12x - 5
f(-1) = 12.(-1) -5
f(-1) = -12 -5 
f(-1) = -17
******************